Industrial Cooperation, Knowledge Sources and the Role of Public Sector in Manufacturing Firms: Case of Spain and Portugal - Anderson, Henry Junior; Gyamfi, Solomon; Stejskal, Jan (Masarykova univerzita, 2019)
Public Funding for firms has been argued as a catalyst for firms’ cooperative and knowledge generative activities in contemporary knowledge-based economies. As innovation potential is widely poised as regional competitive ability, firms’ cooperation with partners have been revered as a preliminary activity to establishing networks whilst sharing diverse knowledge from partners involved to initiate or even mediate innovation. Using data from Community Innovation Survey (2012-2014) and SEM analysis on Spanish and Portuguese manufacturing firms, the paper assesses the relevance of public funds on cooperation tendencies of firms, knowledge sourcing from partners and eventually, the moderator role played by cooperation in appropriating public funds for knowledge acquisition. It was found that public funding significantly influences cooperation in Spain than in Portugal whilst cooperation was much more influential in sourcing for knowledge from partners in Portugal than in Spain. Results also revealed a slightly higher moderator ability of cooperation in Spain than in Portugal. Country-specific recommendations were further created.
Průmyslová spolupráce, zdroje znalostí a úloha veřejného sektoru ve výrobních firmách: Případ Španělska a Portugalska
Keywords: Public funds; Cooperation; Knowledge; Spain; Portugal; Veřejné fondy; Spolupráce; Znalost; Španělsko; Portugalsko